Web metrics for library and information professionals - Stuart, David (David Patrick) (London : Facet Publishing, 2014)
This is a practical guide to using web metrics to measure impact and demonstrate value. The web provides an opportunity to collect a host o f different metrics, from those associated with social media accounts a nd websites to more traditional research outputs. This book is a clear guide for library and information professionals as to what web metrics are available and how to assess and use them to make informed decisions and demonstrate value. As individuals and organizations increasingly u se the web in addition to traditional publishing avenues and formats, t his book provides the tools to unlock web metrics and evaluate the impa ct of this content. The key topics covered include: bibliometrics, webo metrics and web metrics; data collection tools; evaluating impact on th e web; evaluating social media impact; investigating relationships betw een actors; exploring traditional publications in a new environment; we b metrics and the web of data; the future of web metrics and the librar y and information professional. The book will provide a practical intro duction to web metrics for a wide range of library and information prof essionals, from the bibliometrician wanting to demonstrate the wider im pact of a researcher's work than can be demonstrated through traditiona l citations databases, to the reference librarian wanting to measure ho w successfully they are engaging with their users on Twitter. It will b e a valuable tool for anyone who wants to not only understand the impac t of content, but demonstrate this impact to others within the organiza tion and beyond.--
1. Introduction. Metrics -- Indicators -- Web metrics and Ranganatha n's laws of library science -- Web metrics for the library and informat ion professional -- The aim of this book -- The structure of the rest o f this book -- 2. Bibliometrics, webometrics and web metrics. Web metri cs -- Information science metrics -- Web analytics -- Relational and ev aluative metrics -- Evaluative web metrics -- Relational web metrics -- Validating the results -- 3. Data collection tools. The anatomy of a U RL, web links and the structure of the web -- Search engines 1.0 -- Web crawlers -- Search engines 2.0 -- Post search engine 2.0: fragmentatio n -- 4. Evaluating impact on the web. Websites -- Blogs -- Wikis -- Int ernal metrics -- External metrics -- A systematic approach to content a nalysis -- 5. Evaluating social media impact. Aspects of social network sites -- Typology of social network sites -- Research and tools for sp ecific sites and services -- Other social network sites -- URL shortene rs: web analytic links on any site -- General social media impact -- Se ntiment analysis -- 6. Investigating relationships between actors. Soci al network analysis methods -- Sources for relational network analysis -- 7. Exploring traditional publications in a new environment. More bib liographic items -- Full text analysis -- Greater context -- 8. Web met rics and the web of data. The web of data -- Building the semantic web -- Implications of the web of data for web metrics -- Investigating the web of data today -- SPARQL -- Sindice -- LDSpider: an RDF web crawler -- 9. The future of web metrics and the library and information profes sional. How far we have come -- The future of web metrics -- The future of the library and information professional and web metrics.
Includes bibliographical references (pages 177-193) and index.
Keywords: Resource description & access; Webometrics; Data mining; Library science; Internet; Bibliotheques; Services d'information.; Fouille de donnees; Analyse statistique; Evaluation